Meningkatkan Minat Membaca Anak-anak Melalui Sudut Baca Kreatif Berbasis Budaya Lokal SD Negeri 0207 Desa Pangirkiran Dolok - Era Mutiah; Muttiah Tanjung; Hotmarito Hasibuan; Nirmala Daulay; Siti Opsah Nasution (Jurnal Transformasi Pendidikan Indonesia, 2025)
This study aims to evaluate the effectiveness of implementing a creative reading corner based on local culture in increasing students' reading interest at SD Negeri 0207 in Pangirkiran Dolok Village. The research background is based on students' low reading interest influenced by the dominance of gadget use and a lack of interest in conventional reading materials. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation with the principal, teachers, and students. The results show that a creative reading corner designed attractively and containing reading material highlighting local folktales, legends, and traditions creates a comfortable, enjoyable, and relevant literacy environment for students. Students become more enthusiastic about reading, discussing, and recognizing local cultural values. The teacher's active role in guiding, assisting, and implementing interactive reading activities also contributes significantly to building sustainable literacy habits.